ANALISIS PENGARUH BONUS DEMOGRAFI TERHADAP PERTUMBUHAN EKONOMI - Hermawan, Irwan (Jurnal Aktiva : Riset Akuntansi dan Keuangan, 2019)
The purpose of this study was to examine the effect of demographic variables on economic growth in North Kalimantan Province, including the influence of the Dependency Ratio variable on the economic growth of North Kalimantan province, the effect of the TPAK variable (labor force participation rate) on provincial economic growth North Kalimantan and the influence of the unemployment rate variable on the economic growth of the province of North Kalimantan. This study uses a quantitative approach. The data used in this study is secondary data which is Panel Data, which is a combination of time series data (Time Series) and cross section data (Cross Section). The data was collected from the Regional Statistics Data of the Province of North Kalimantan, including Statistics Data on the Districts of Malinau, Bulungan, Tana Tidung, Nunukan and the City of Tarakan. The results showed that the impact of the variables associated with demographic bonus together had a significant effect on the economic growth of the regency-city in North Kalimantan Province, but the effect of each of the independent variables was different. For the Dependency Ratio, the effect is negative and significant, the Labor Force Participation Rate has a negative and not significant effect, the Unemployment Rate has a positive and not significant effect. Limitations in this study are limited secondary data, namely data obtained from 2014 to 2018, this is because the province of North Kalimantan is the youngest province in Indonesia. The implication of this research is that the North Kalimantan Provincial Government can take advantage of the Demographic Bonus, this is because the Demographic Bonus especially the Dependency Ratio Variable has a significant effect on economic growth (GRDP) in North Kalimantan Province, and the North Kalimantan Regional Government can take policies so that the dependency ratio decreases and will have a positive effect on regional economic growth in North Kalimantan Province.